La manutenzione e riabilitazione delle dighe ed opere idrauliche associate (GEOmedia, 2016)
ITCOLD Italian Committee on Large Dams is a cultural and scientific association that proposes him to promote and to facilitate the study of all the connected problems with the dams, their realization and their operation. The Italian patrimony in this field is of everything respect in the international panorama. The structures operating on our territory are over 500 with a 60 year-old middle age. The appointment of the technicians of the countries developed as ours is for the most turned to the maintenance, to the increase of the safety and the optimization of this typology building that it is often by now considered integral part of the natural environment in which is inserted. Two Groups of Job have produced an investigation on the experiences concerning rehabilitation of the dams and of the hydraulic works to them associate giving a general picture of the status of the sector, The Permanent observatory is finalized to the harvest and the diffusion of the whole further refurbishment activities applied right now, favoring the technical debate and the growth of the know how in the community of the associates.